KEBIJAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PENGHINAAN / PENCEMARAN NAMA BAIK MELALUI INTERNET DI INDONESIA SEBAGAI CYBERCRIME - Syarifuddin Syarifuddin (AkMen JURNAL ILMIAH, 2018)
Through a criminal law policy to provide protection for users and providers of information technology from cybercrime, the government designs and ratifies Law No. 11 of 2008 concerning Information and Electronic Transactions (UU ITE). This Act further emphasizes the existence of Indonesia as one of the countries that is serious in fighting cybercrime. But in practice, this Law has become a rule that shackles the exercise of freedom of expression. This happened because of the existence of Article 27 paragraph (3) which regulates criminal acts of insult / defamation as part of cybercrime. In fact, the act of humiliation has been clearly regulated, clearly and concretely in the Criminal Code and the Civil Code. In legal politics, it is not easy to establish an act as a criminal act and must first go through several in-depth review processes. The problems discussed are: What is the criminal law policy against criminal acts of insult / defamation through the internet in Indonesia? How is the guarantee of the protection of freedom of expression on the internet associated with the existence of criminal acts of insult / defamation in Law No. 11 of 2008 concerning Information and Electronic Transactions as amended to Act Number 19 of 2016? This research is a normative juridical research with a doctrinallegal approach. As a normative system, the law must be viewed comprehensively such as principles, norms and meta norms. Criminal law policy against criminal acts of insult in cyberspace is actually a duplication of the Insult provisions stipulated in the Criminal Code, this is clearly contrary to the lex scricta principle, and lex certa. Making criminal acts of humiliation as a cyber crime with a relatively heavier crime rather than giving a deterrent effect but instead creates a chilling effect on freedom of opinion and expression. Removing Article 27 Paragraph (3) in the ITE Law is a choice that needs to be done by the Government by implementing a return to the balance of conditions for criminal acts of humiliation in the form of good name recovery and applying compensation that needs to be associated with the Criminal Code Bill relating to criminal prosecution.